Sofferenza mentale e cambiamento psichico in contesti non clinici il recupero della genitorialità critica in ambito giuridico - 1 Marco Architravo, 2 Massimiliano Troisi, 3 Daniela Cantone (Marp Edizioni, 2019)
The authors propose a reflection on how psychic change can also occur in non-clinical contexts, when a critical event involves the intervention of institutions attentive to psychological aspects. An emblematic example is the questioning of parenting skills within juvenile court proceedings. The integrated approach, between normative needs and psychological phenomena, if on the one hand suggests a reorganization of the functions of breeding and care, but also opportunities, on the other hand allows a reformulation of parts of one's personal and parental identity. In particular it describes what happens when the intervention of the Judicial Authority, together with that of the social and social health services, takes on the function of supporting and resolving the crisis rather than the exclusive judgment and control. By reading the guideline currently applicable in force concerning psychological pathways for the strengthening of critical parenting, the salient phases that characterize the judicial procedure as a moment within which new emotional resonances and renewed awareness of processes can emerge of change